Intragastric Balloon Offers Surgical Alternate for Treatment of Obesity: The REDUCE Trial - Nichols, Emma Hitt (MD Conference Express, 2014)
Saline-filled intragastric balloons are a possible option for patients who are not suitable candidates for bariatric surgery or do not want it. This article presents the results of A Prospective, Randomized Multicenter Study to Evaluate the Safety and Efficacy of the ReShape Duo Intragastric Balloon System in Obese Subjects [REDUCE; NCT01673698].